Neuromodulatory effect of progesterone on the dopaminergic, glutamatergic, and GABAergic activities in a male rat model of Parkinson's disease - Casas, Sebastián Marcelo (2013)
Objectives: Progesterone has been reported to have a neuroprotective role in depression-like rats in a hemiparkinsonian model of the disease. In this work, we investigate if this hormone affects the three principal neurochemicals striatal systems (dopaminergic, glutamatergic, and GABAergic) that are involved in the physiopathology of the disease in a hemiparkinsonim male rat model at 8 weeks post-chemical injury. Methods: For this purpose, we design three experimental groups: (1) sham group; (2) hemiparkinsonian group; and (3) hemiparkinsonian group subcutaneously injected with progesterone at 7 days post- chemical injury. Animals were tested in an automated rotational device at 8 weeks post-chemical injury. After behavioral test, Kz-evoked [3H]-dopamine, [3H]-glutamate, and [3H]-gamma aminobutyric acid release from striatum slices were analyzed by superfusion experiments. Results: The hemiparkinsonian group showed distinctive alterations that are produced by neurodegenera- tion of left nigrostriatal dopaminergic pathway by 6-hydroxydopamine hydrobromide (6-OHDA). On the other hand, the administration of progesterone 7 days after the injection of the neurotoxin was able to (1) improve the Kz-evoked [3H]-dopamine release from the damaged striata (left); (2) avoid significant increase in the Kz-evoked [3H]-glutamate release from the left striata; and (3) progesterone does not modify the Kz-evoked [3H]-gamma aminobutyric acid release from the left striata. Discussion: These results suggest that progesterone does have neuroprotective and neuromodulatory effects on striatal neurotransmission systems in the hemiparkinsonian male rats. The possible mechanisms would involve genomic and non-genomic actions of this neuroactive steroid which would modulate the activity of dopaminergic, glutamatergic, and GABAergic pathways.